KAJIAN TENTANG HAK KESEHATAN PEKERJA PERKEBUNAN SAWIT PADA KOPERASI PESANTREN DARUSSALAM DESA SARAN KABUN KABUPATEN ROKAN HULU - Habibur Rahman; Hayatul Ismi; Dasrol Dasrol (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2019)
Labor is one of the important factors in national development, because it requires efforts to foster,direct, facilitate, and protect workers to create welfare related to what they do. This protection is alsorelated to the risk of workplace accidents that often occur. This protection also occurred in severalcompanies, one of them was the Pesantren Darussalam Cooperative in Saran Kabun Village, Rokan HuluRegency. In practice the rights of workers in the health sector are not carried out or the difficulty is to getan insurance claim. This study discusses the implementation of health rights for workers and what are theobstacles faced in implementing the rights of workers in the Pesantren Darussalam Cooperative.The type of research used is sociological legal research, which is a study that directly descendslocation located in the Pesantren Darussalam Cooperative in Rokan Hulu Regency with a qualitativemethod, where data collection is done by questionnaires and direct interviews to the field so as to be able toexplore information about the implementation of health rights the employees.The results obtained from this study state that the implementation of the health rights of thePesantren Darussalam Cooperative workers has not fully run properly due to the lack of guarantees ofhealth rights and other rights for workers so that the rights of the Pesantren Darussalam Cooperativeworkers are not implementedKeywords: Labor, Cooperatives, Health, protection.